Quantitative Determination of the Amino Acids and other Ninhydrin Positive Substances in Normal Human Platelets - Gross, R; Gerok, W (Thrombosis and Haemostasis, 1961)
In normal human platelets twenty amino acids and additionally taurine, phosphoethanolamine and phosphoserine were determined on a quantitative basis, using elution chromatography on ion exchangers.The highest molar share goes to taurine, glutamic acid, alanine, aspartic acid, proline and serine. The other amino acids can be found in free form only in a low concentration in platelets.The connection of these results with other investigations on the metabolism is discussed.